Electromechanical Strain Responses of SEBS/CB and SEBS/SWCNT Composites - Kim, Il Jin; Jung, Jiyoung; Hong, Soon Man; Koo, Chong Min (TAYLOR & FRANCIS LTD, 2012)
Electromechanical strain responses of poly (styrene-b-ethylbutylene-b-styrene) (SEBS) / carbon black (CB) composites and SEBS/single wall carbon nanotube (SWCNT) composites were investigated. The electric field induced thickness strains s(z) of the composites increased with the conductive filler content at the low filler concentration region and then showed the maximum. s(z) represents relative thickness change relative to the initial thickness of the composite film. A further increase of the filler concentration caused a decrease in the actuation strain. The SEBS/SWCNT showed a larger s(z) than SEBS/CB at the same filler content.